Premios monetarios a la escolaridad de nivel licenciatura en el mercado laboral formal e informal: el caso de México 2018 - Cortés Luna, Luis Xavier (Universidad Autónoma Metropolitana, 2020)
In this research, an updated theoretical framework of the main arguments of the economics of education and work is systematized, with respect to the relationship between undergraduate education and labor income of salaried workers, formal and informal (Becker, 1975; Shultz, 1972; Arrow, 1973; Spence, 1974; Carnoy, 2006; Tokman, 1990; Lewis, 1960; Rosen, 1986; Maloney, 1998). The monetary awards for schooling are estimated, corresponding to employed and subordinate workers, formal and informal, with bachelor's studies, in Mexico 2018. For this, the micro data of the National Survey of Income and Households (ENIGH) 2018, new series. Furthermore, the main differences between the monetary reward for schooling and the internal rate of return (IRR) for education are raised. It is concluded that the labor market rewards the different attributes of workers, including schooling. The average monetary award for an additional year of schooling at the upper secondary or undergraduate levels, without differentiating between these two levels, is estimated at 14.27%. The average monetary award for an additional year of study in the bachelor's degree is 11.63%. This award, but for workers in the formal sector of the labor market, is estimated at 13.91% and less than 11.63% for workers in the informal sector. Therefore, it is concluded that the monetary award for schooling at the undergraduate level is approximately 2.28% higher for formal workers than for informal workers. For its part, the monetary premium for formality with respect to informality is 52.25%. The estimates obtained in this research on the monetary award for schooling at the undergraduate level for the labor market as a whole are similar to the award estimated at 13.33% for Mexico 1989 (Bracho and Zamudio, 1994). The estimates obtained on the monetary awards for schooling at the undergraduate level for each sector of the labor market are different from those estimated by authors such as Llamas (2019), which estimates the awards (or income differentials) for higher education in 7.5% and 5.8% for the formal and informal sectors, respectively, in the period 2005-2017. Therefore, this research constitutes an additional reference on the returns to education in Mexico.; En la presente investigación se sistematiza un marco teórico actualizado de los principales argumentos de la economía de la educación y economía del trabajo, con respecto a la relación entre educación de nivel licenciatura e ingresos laborales de los trabajadores ocupados asalariados, formales e informales (Becker, 1975; Shultz, 1972; Arrow, 1973; Spence, 1974; Carnoy, 2006; Tokman, 1990; Lewis, 1960; Rosen, 1986; Maloney, 1998). Se estiman los premios monetarios a la escolaridad, correspondientes a los trabajadores ocupados y subordinados, formales e informales, con estudios de licenciatura, en México 2018. Para ello, se utilizan los micro datos de la Encuesta Nacional de Ingresos y Gastos de los Hogares (ENIGH) 2018, nueva serie. Además, se plantean las principales diferencias entre el premio monetario a la escolaridad y la tasa interna de retorno (TIR) de la educación. Se concluye que el mercado laboral premia los distintos atributos de los trabajadores, entre ellos la escolaridad. El premio promedio monetario a un año adicional de escolaridad en los niveles de educación media superior o licenciatura, sin diferenciar entre estos dos niveles, se estima en 14.27%. El premio monetario promedio a un año adicional de estudio en la licenciatura es 11.63%. Este premio, pero para los trabajadores del sector formal del mercado laboral, se estima en 13.91% y en menos de 11.63% para los trabajadores del sector informal. Por lo tanto, se concluye que el premio monetario a la escolaridad en el nivel de licenciatura, es aproximadamente 2.28% mayor para los trabajadores formales que para los trabajadores informales. Por su parte, el premio monetario a la formalidad con respecto a la informalidad es de 52.25%. Las estimaciones obtenidas en esta investigación sobre el premio monetario a la escolaridad en el nivel de licenciatura para el mercado laboral como un todo, son similares al premio estimado en 13.33% para México 1989 (Bracho y Zamudio, 1994). Las estimaciones obtenidas sobre los premios monetarios a la escolaridad en el nivel de licenciatura para cada sector del mercado laboral son distintas a las estimadas por autores como Llamas (2019), el cual estima los premios (o diferenciales de ingresos) de la escolaridad superior en 7.5% y 5.8% para el sector formal e informal, respectivamente, en el periodo 2005-2017. Por lo tanto, la presente investigación constituye un referente adicional sobre los rendimientos de la educación en México.